Assessment of Drinking Water Quality in Different Water Sources and its Impact on Downstream Community Health around Woldia Town, Ethiopia - Teshome, Gizachew; Bizualem, Endalikachew (International Journal of Geography and Geology, 2019)
Water is one of the most vital natural resources known on the earth. The quality of drinking water is degrading by various sources of contaminants. The analysis of Bacteriological and physio-chemical quality from hand dug and open stream/rivers around Woldia town was conducted from March, 2018 to September, 2018. Sixty water samples were drown from a total of ten hand dug wells located around town and analysed for total coliforms, fecal coliforms and E.coli using multiple tube fermentation (MTF) method. Physico chemical parameter (temperature and electrical conductivity) by conductivity meter 4200 UK, Turbidity by turbidity meter 2100Q, ammonia, Sulfate and pH determined by photometer, E. coli 11 (18.3%) was detected from both sources of samples and 60 (100%) water samples were analysed had total coliform and also 48 (80%) drinking water samples were analyzed had fecal coliform. There was a statistically significant difference among water sources with respect to TC and TTC (p < 0.05) and there was a statistically significant positive and negatively correlation between coliform counts and physicochemical parameter (p < 0.01) and (p < 0.05). Most water sources didn’t satisfy the turbidity values recommended by World Health Organization. Average value of temperature, pH, electrical conductivity, turbidity, Sulphate and ammonia were 22.5±1.11oC, 98±0.38, 40.40±10.67μs/cm,7.3±6.15 NTU, 0.167±0.19mg/l, 3.64±0.84 mg/l, respectively. Water supplies at open hand dug and protected hand dug were contaminated with coliforms. The water sources were heavily contaminated which suggested poor protection and sanitation practice in the water sources are the causes for contamination.